A new route for the recycling of spent lithium-ion batteries towards advanced energy storage, conversion, and harvesting systems. (October 2022) - Natarajan, Subramanian; Krishnamoorthy, Karthikeyan; Sathyaseelan, Arunprasath; Mariappan, Vimal Kumar; Pazhamalai, Parthiban; Manoharan, Sindhuja; Kim, Sang-Jae
Abstract: A new, sustainable, recycling technology is developed for the first time by reusing all the components of spent LIBs (anode, cathode, separator, and current collectors) towards energy storage, conversion, and harvesting applications, considering the environmental concerns and valuable resources. The graphite anode and metallic aluminium cases are effectively recycled to produce two-dimensional graphene sheets that are reutilized for 3.0 V supercapacitors exhibit a high energy density of 31.9 Wh kg –1 with long cycle life. The spent cathode is regenerated as Ni–Mn–Co–oxide and employed as a novel bifunctional electrocatalyst for overall water splitting in alkaline electrolytes, which requires a low voltage of 1.58 V to achieve a current density of 10 mA cm −2 . The metallic current collectors and polymeric separator are reused to construct a triboelectric nanogenerator, produces a maximum voltage of ~40 V and a current of ~160 nA with a peak power of 3 μW. Hence, this study provides a feasible strategy of recycling all the components from spent LIBs to develop next-generation energy storage, conversion, and harvesting devices. Graphical Abstract: For the first time, a new methodology is developed for the spent lithium-ion battery recycling towards supercapacitor, water splitting, and triboelectric nanogenerator applications by reusing cathode, anode, separator, and metallic cases components. The obtained result encourages the researchers to construct more advanced energy devices using the spent lithium-ion battery components. ga1 Highlights: Almost all components of spent lithium-ion batteries have been recycled and reused. Graphene from anode employed as electrodes for building 3.0 V supercapacitor. The regenerated cathode material achieves 10 mA cm −2 with 1.58 V in water splitting. Recovered current collectors and separator employed for nanogenerator fabrication. 3R concept has been employed to construct energy devices from spent LIB sources.